Development of Monitoring System Based on Internet of Things (IoT) for Freshwater Prawn Farming - Rami, Muhammad Irham; Majid, Huda (Journal of Advanced Industrial Technology and Application, 2022)
Aqua-farming or water farming is an aquatic counterpart to agriculture or ground farming. It is one of methods to make out foods or commercial product. With the current incompetent aqua-farming activities such as labour energy consumption to monitor the water quality and to change the water in the tank in schedule so that this project is important to tackle down the problems stated. This project aimed to reduce the incompetency of water quality monitoring process and the water changing process by developing a vertical freshwater prawn tank to reduce space with an automated water changing and IoT based monitoring system. The autonomous system implemented with solenoid valve and waterpump will recycle the water from the prawn tanks with the clean water from the reservoir tank. The monitoring system employs ultrasonic sensor and waterproof temperature sensor that will monitor the water level in the prawn tanks and the temperature of the water respectively that will be visualized in the Thingspeak Channel regularly. This project will be implemented as a prototype with an IoT technology for the freshwater prawn farming activity using low-cost embedded devices like Arduino Mega2560, ESP8266 Wi-Fi module and the RTC module. The value from the sensors’ reading will be visualized in the Thingspeak Channel display